Immunoexpression of TS, p53, COX2, EGFR, MSH6 and MLH1 biomarkers and its correlation with degree of differentiation, tumor staging and prognostic factors in colorectal adenocarcinoma: a retrospective longitudinal study - Batista, Wilson Roberto (2019)
BACKGROUND: There are cases of colorectal tumors that, although small, show more aggressive evo-lution than large tumors. This motivated us to study whether there are any proteins capable of alerting about these changes. The aim here was to correlate the immunoexpression of the TS, p53, COX2, EGFR, MSH6 and MLH1 biomarkers in tumors in patients with colorectal adenocarcinoma, with the degree of cell differentiation, tumor staging and clinical-pathological prognostic factors. DESIGN AND SETTING: Retrospective observational study at a public tertiary-level hospital. METHODS: We analyzed tissue-microarray paraffin blocks of tumor tissues that had been resected from 107 patients. We used Fisher’s exact test to study associations between tumor differentiation/staging and the immunoexpression of biomarkers. We also used Kaplan-Meier estimation, the log-rank test and the adjusted Cox regression model to investigate the patients’ overall survival (in months) according to bio-markers and disease-free interval. RESULTS: The degree of tumor differentiation and tumor staging were not associated with the biomark-ers, except in cases of patients in stages III or IV, in which there was a correlation with MLH1 expression (P = 0.021). Patient survival and disease-free interval were not associated with the biomarkers. CONCLUSION: There were no associations between the degree of tumor differentiation, staging, length of survival or disease-free interval and the immunoexpression of the TS, p53, COX2, EGFR or MSH6 tumor markers. In advanced cases of colorectal adenocarcinoma (stages III and IV), there was a higher percentage of MLH1-negative results.